A kind of building joint sealing material and its preparation process
By optimizing the components of polyurethane sealing materials, using raw materials such as polyurethane glue, silane, epoxy resin and activated calcium carbonate, a building joint sealing material was prepared, which solved the decline in performance of polyurethane sealing glue in humid or ultraviolet environments. The problem is that high mechanical properties, excellent bonding properties and good aging resistance are achieved.
Patent Information
- Application Number
- CN202310367812.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-07
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2043-04-07
AI Technical Summary
Existing polyurethane sealants are prone to softening, molecular chain breakage in humid or ultraviolet environments, and their mechanical properties are degraded, and their adhesiveness on the surface of non-porous and non-reactive substrates are insufficient, so their mechanical properties need to be improved.
By optimizing the components of polyurethane sealing materials, a building joint sealing material is prepared by using raw materials such as polyurethane-based glue, plasticizer, filler, reinforcement additive, catalyst, latent curing agent, water removal agent and polyamide wax. The material is compositely modified with silane and epoxy resin, activated calcium carbonate is used as filler, and anti-aging agent is loaded on the inorganic material to form a composite material to improve bonding performance and weather resistance.
The prepared sealing materials have excellent mechanical properties and bonding properties. After 70℃ thermal aging, 70℃×95%RH humidity and heat aging and ultraviolet aging tests, the mechanical properties decline by small, high stability, and excellent aging resistance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building sealing materials, in particular to a building joint sealing material and a preparation process thereof. Background Art
[0002] When assembling the prefabricated exterior walls of prefabricated concrete buildings, a large number of assembly joints will be left. Water leakage in the joints can easily cause steel corrosion or wall peeling, which in turn affects the safety of the building. Therefore, joint waterproofing is very important, and joint sealant materials are an important line of defense for assembly joint waterproofing.
[0003] At present, the commonly used sealing materials include silicone sealant, silane modified polyether sealant, polyurethane sealant, etc. Among them, silicone sealant is a paste made of polydimethylsiloxane as the main raw material, with crosslinking agent, plasticizer, coupling agent, catalyst, and filler mixed in a vacuum state. It has stable performance, super strong resistance to ultraviolet rays, ozone, and aging, and good elasticity, small shrinkage, and excellent high and low temperature resistance. However, it has low strength, poor adhesion to bonding materials, and is expensive. Silane modified polyether sealant has excellent weather resistance, stable structure, and excellent bonding performance. Its disadvantage is that siloxane has poor alkali resistance, and it is easy to degrade and debond due to alkali when used on concrete substrates. The product has poor resilience. In addition, the resin and the matching crosslinking accelerator are expensive. Compared with the above two sealants, polyurethane has the advantages of high mechanical strength, excellent wear resistance, strong bonding performance, good elasticity, etc., and it has a high cost performance, so it has a wide range of applications. The problems with polyurethane sealants are: it is easy to release CO2 gas during curing to cause bubbling of the adhesive layer, and its resistance to moisture and heat and aging performance are relatively poor. In a humid, hot or ultraviolet environment, the elastomer is prone to softening, molecular chain breakage, and mechanical property degradation after curing. The adhesion on the surface of non-porous and non-reactive substrates is insufficient, and its mechanical properties need to be further improved. Summary of the invention
[0004] In view of this, the purpose of the present invention is to provide a building joint sealing material with excellent weather resistance and mechanical properties in view of the deficiencies in the prior art, and to optimize its components. The finally prepared sealing material has excellent mechanical properties and bonding properties, and has high stability and excellent aging resistance after 70°C heat aging, 70°C×95%RH wet heat aging and UV aging tests.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] A building joint sealing material is prepared from the following raw materials in parts by weight: 100 parts of polyurethane base glue, 12-15 parts of plasticizer, 25-30 parts of filler, 8-10 parts of reinforcing auxiliary agent, 0.08-0.1 parts of catalyst, 2.8-3 parts of latent curing agent, 1-1.5 parts of water remover and 1-1.5 parts of polyamide wax.
[0007] Furthermore, the plasticizer is dioctyl phthalate or diisodecyl phthalate, the catalyst is dibutyltin dilaurate, the latent curing agent is ALT402, and the dehydrating agent is p-toluenesulfonyl isocyanate.
[0008] Furthermore, the filler is activated calcium carbonate, and the preparation process of the activated calcium carbonate is: putting calcium carbonate into a ball mill, adding 1-2% KH550 and 1-2% stearic acid by weight of calcium carbonate respectively, and ball milling at 500r / min for 30 minutes to obtain activated calcium carbonate.
[0009] Furthermore, the polyurethane adhesive is prepared by the following steps:
[0010] (1) Add polyether diol, polyether triol and epoxy resin into a three-necked flask, stir, heat to 120-125°C and vacuum dry for 1 hour;
[0011] (2) Cooling to 80°C, adding diphenylmethane diisocyanate, and polymerizing at 80-85°C for 3 hours; then adding polydimethylsiloxane and continuing to stir and react for 1 hour to obtain a polyurethane-based adhesive;
[0012] The weight ratio of the polyether diol, polyether triol, diphenylmethane diisocyanate, epoxy resin and polydimethylsiloxane is 6:10:3:1:1.5-2.
[0013] Furthermore, the reinforcing agent is a composite material prepared by loading an antioxidant on an inorganic material, and its preparation method includes the following steps: dispersing the inorganic material in an acetone solution of the antioxidant 4010NA, evacuating the solution and soaking and adsorbing the solution for 30-60 minutes, then filtering, drying and grinding the solution to obtain the product; the weight ratio of the inorganic material to the antioxidant 4010NA is 4:1.
[0014] Furthermore, the inorganic material is prepared by the following steps:
[0015] (1) After removing impurities from sepiolite powder, the sepiolite powder is mixed with a 3 mol / L hydrochloric acid solution at a weight ratio of 1:60 at 80°C and stirred for 8-10 hours, and then filtered, washed, dried, and ground to obtain acidified sepiolite; the acidified sepiolite is evenly mixed with deionized water at a weight ratio of 1:200, and then hydrothermally reacted at 150°C for 8-10 hours, and then filtered, washed, dried, and ground to obtain sepiolite fiber;
[0016] (2) Prepare 1 L of 0.50 mol / L Zn2SO4·7H2O solution, add 150 g of sepiolite fiber and stir evenly, slowly add 0.5 L of 1.6 mol / L NaOH solution while stirring, then add 1.5-2% KH550 by weight of the sepiolite fiber, place the mixed system in a water bath at 60°C and continue to age for 48 h, filter and dry, and calcine at 1050°C for 5 h to obtain an inorganic material.
[0017] Furthermore, the impurity removal process of the sepiolite powder in the step (1) is as follows: the sepiolite powder is mixed with water in a weight ratio of 1:10-15, and then allowed to stand and soak for 24 hours, and then stirred for 3 hours; allowed to stand and precipitate, and impurities at the bottom are removed during the filtration process; the filtration product is mixed with water in a weight ratio of 1:10, and then 0.2-0.3wt% of sodium hexametapolyphosphate is added and stirred for 1 hour, and allowed to stand for 0.5 hour, and the upper suspension is filtered and dried and ground.
[0018] A preparation process of a building joint sealing material comprises the following steps: adding polyurethane base glue, filler and reinforcing auxiliary agent into a dispersion kettle and dispersing for 1 hour, adding other raw materials and mixing for 30-40 minutes, and discharging to obtain a product.
[0019] The beneficial effects of the present invention are:
[0020] 1. In order to improve the weather resistance and mechanical properties of polyurethane sealant, the components of the polyurethane sealant are optimized. The final prepared sealing material has excellent mechanical properties and bonding properties. Moreover, after 70°C heat aging, 70°C×95%RH wet heat aging and UV aging tests, the mechanical properties decrease very little after 672h and 3000h, with high stability and excellent aging resistance.
[0021] 2. The polyurethane base glue is composite-modified with silane and epoxy resin, among which KH550 has excellent water resistance, heat resistance and bonding properties, and low surface free energy. The R-NCO part is converted into alkoxy, which can reduce the generation of gas in the curing process, increase the stability of polyurethane, and increase the bonding performance and heat resistance and aging resistance of polyurethane to the substrate. Moreover, epoxy resin can also react with -NCO, and the epoxy resin is introduced into the cross-linked network structure of the polyurethane molecular chain, which can increase the mechanical properties and stability of the polyurethane structure.
[0022] 3. Filler calcium carbonate uses silane coupling agent KH550 and stearic acid to activate calcium carbonate, which can increase the dispersion performance of the filler in polyurethane on the one hand, and improve its compatibility with polyurethane on the other hand.
[0023] 4. The sealing material of the present application is added with a reinforcing agent, which is prepared by loading an inorganic material with an antioxidant. The inorganic material is a composite of sepiolite fiber and zinc oxide whisker, wherein the sepiolite fiber is prepared by acidifying the sepiolite and then hydrothermally treating it to further increase the specific surface area and adsorption performance of the sepiolite fiber. The diameter of the prepared sepiolite fiber is 100-200nm (grinded to a length of less than 80μm); then the zinc oxide whisker is uniformly loaded on the sepiolite fiber to form an inorganic fiber material; the inorganic fiber material has a certain aspect ratio, is uniformly dispersed in the polyurethane system, has a large contact area with the polyurethane system, generates large friction, and is more likely to absorb external impact energy when external force is concentrated, so it has a stronger reinforcing and toughening effect on polyurethane.
[0024] 5. The antioxidant is vacuum impregnated on the inorganic fiber material. The antioxidant is evenly adsorbed on the inside and surface of the sepiolite fiber and zinc oxide whisker, which can extend the migration time of the antioxidant. Zinc oxide also has the effect of ultraviolet absorption and has significant absorption in the wavelength range of 295-365nm. Therefore, the combination of zinc oxide and antioxidant can further improve the weather resistance of polyurethane. Implementation
[0025] The present invention will be further described below in conjunction with the embodiments. Example 1
[0026] A building joint sealing material is made of the following raw materials in parts by weight: 100 parts of polyurethane base glue, 12 parts of plasticizer, 25 parts of filler, 10 parts of reinforcing auxiliary agent, 0.08 parts of catalyst, 2.8 parts of latent curing agent, 1 part of water removing agent and 1 part of polyamide wax.
[0027] The plasticizer is dioctyl phthalate, the catalyst is dibutyltin dilaurate, the latent curing agent is ALT402, and the water scavenger is p-toluenesulfonyl isocyanate.
[0028] The filler is activated calcium carbonate, and the preparation process of activated calcium carbonate is as follows: put calcium carbonate into a ball mill, add 1% KH550 and 1% stearic acid by weight of calcium carbonate respectively, and ball mill at 500r / min for 30 minutes to obtain activated calcium carbonate.
[0029] The polyurethane base adhesive is prepared by the following steps:
[0030] (1) Add polyether diol (DL2000), polyether triol (3000) and epoxy resin into a three-necked flask, stir and heat to 120-125°C, and vacuum dry for 1 hour (vacuum degree -0.1Mpa);
[0031] (2) Cooling to 80°C, adding diphenylmethane diisocyanate, and polymerizing at 80-85°C for 3 hours; then adding polydimethylsiloxane and continuing to stir and react for 1 hour to obtain a polyurethane-based adhesive;
[0032] The weight ratio of polyether diol, polyether triol, diphenylmethane diisocyanate, epoxy resin and polydimethylsiloxane is 6:10:3:1:1.5. The polyether diol (DL2000), polyether triol (3000) and diphenylmethane diisocyanate are subjected to vacuum dehydration treatment before use.
[0033] The reinforcing agent is a composite material prepared by loading an antioxidant on an inorganic material, and its preparation process includes the following steps: dispersing the inorganic material in an acetone solution of the antioxidant 4010NA, evacuating the solution, impregnating and adsorbing the solution for 30-60 minutes, and then filtering, drying, and grinding the solution to obtain the product; the weight ratio of the inorganic material to 4010NA is 4:1, and the weight ratio of the antioxidant 4010NA to acetone is 1:6.
[0034] The above inorganic material is prepared by the following method:
[0035] (1) After removing impurities from sepiolite powder, the sepiolite powder was mixed with a 3 mol / L hydrochloric acid solution at a weight ratio of 1:60 at 80°C and stirred for 8 hours, and then filtered, washed, dried, and ground to obtain acidified sepiolite; the acidified sepiolite was evenly mixed with deionized water at a weight ratio of 1:200, and then hydrothermally reacted at 150°C for 8 hours, filtered, washed, dried, and ground until the length was less than 80 μm, to obtain sepiolite fibers;
[0036] (2) Prepare 1 L of 0.50 mol / L Zn2SO4·7H2O solution, add 150 g of sepiolite fiber and stir evenly, slowly add 0.5 L of 1.6 mol / L NaOH solution while stirring, and then add KH550 (2% by weight of the sepiolite fiber). Place the mixed system in a water bath at 60°C and continue to age for 48 h. After filtering and drying, calcinate at 1050°C for 5 h to obtain an inorganic material.
[0037] The specific method of removing impurities from the sepiolite powder in step (1) is as follows: the sepiolite powder is mixed with water in a weight ratio of 1:10, the mixture is allowed to stand and soak for 24 hours, and then stirred for 3 hours; the mixture is allowed to stand and settle, and impurities at the bottom are removed during the filtration process; the filtration product is mixed with water in a weight ratio of 1:10, and then 0.2wt% sodium hexametapolyphosphate is added and stirred for 1 hour, the mixture is allowed to stand for 0.5 hour, the upper suspension is filtered, and then dried and ground.
[0038] The specific preparation process of the above-mentioned building joint sealing material is: adding polyurethane base glue, filler and reinforcing auxiliary agent into a dispersion kettle and dispersing for 1 hour, adding other raw materials and mixing for 30-40 minutes, and discharging to obtain the product. Example 2
[0039] A building joint sealing material is prepared from the following raw materials in parts by weight: 100 parts of polyurethane base glue, 13 parts of plasticizer, 26 parts of filler, 9.5 parts of reinforcing auxiliary agent, 0.08 parts of catalyst, 2.9 parts of latent curing agent, 1.2 parts of water remover and 1.2 parts of polyamide wax.
[0040] The plasticizer is diisodecyl phthalate, the catalyst is dibutyltin dilaurate, the latent curing agent is ALT402, and the water scavenger is p-toluenesulfonyl isocyanate.
[0041] The filler is activated calcium carbonate, and the preparation process of activated calcium carbonate is as follows: put calcium carbonate into a ball mill, add 1.5% KH550 and 1.5% stearic acid by weight of calcium carbonate respectively, and ball mill at 500r / min for 30 minutes to obtain activated calcium carbonate.
[0042] The polyurethane base adhesive is prepared by the following steps:
[0043] (1) Add polyether diol (DL2000), polyether triol (3000) and epoxy resin into a three-necked flask, stir and heat to 120-125°C, and vacuum dry for 1 hour (vacuum degree -0.1Mpa);
[0044] (2) Cooling to 80°C, adding diphenylmethane diisocyanate, and polymerizing at 80-85°C for 3 hours; then adding polydimethylsiloxane and continuing to stir and react for 1 hour to obtain a polyurethane-based adhesive;
[0045] The weight ratio of polyether diol, polyether triol, diphenylmethane diisocyanate, epoxy resin and polydimethylsiloxane is 6:10:3:1:1.6. Polyether diol (DL2000), polyether triol (3000) and diphenylmethane diisocyanate are subjected to vacuum dehydration treatment before use.
[0046] The reinforcing agent is a composite material prepared by loading an antioxidant on an inorganic material, and its preparation process includes the following steps: dispersing the inorganic material in an acetone solution of the antioxidant 4010NA, evacuating the solution, impregnating and adsorbing the solution for 30-60 minutes, and then filtering, drying, and grinding the solution to obtain the product; the weight ratio of the inorganic material to 4010NA is 4:1.
[0047] The above inorganic material is prepared by the following method:
[0048] (1) After removing impurities from sepiolite powder, the mixture was mixed with 3 mol / L hydrochloric acid solution at a weight ratio of 1:60 at 80°C and stirred for 9 hours, and then filtered, washed, dried and ground to obtain acidified sepiolite; the acidified sepiolite was evenly mixed with deionized water at a weight ratio of 1:200, and then hydrothermally reacted at 150°C for 9 hours, and then filtered, washed, dried and ground to obtain sepiolite fiber;
[0049] (2) Prepare 1 L of 0.50 mol / L Zn2SO4·7H2O solution, add 150 g of sepiolite fiber and stir evenly, slowly add 0.5 L of 1.6 mol / L NaOH solution while stirring, and then add 1.5% KH550 by weight of the sepiolite fiber. Place the mixed system in a water bath at 60°C for 48 h, filter, dry, and calcine at 1050°C for 5 h to obtain an inorganic material.
[0050] The specific method of removing impurities from the sepiolite powder in step (1) is as follows: the sepiolite powder is mixed with water in a weight ratio of 1:11, the mixture is allowed to stand and soak for 24 hours, and then stirred for 3 hours; the mixture is allowed to stand and settle, and impurities at the bottom are removed during the filtration process; the filtration product is mixed with water in a weight ratio of 1:10, and then 0.25wt% sodium hexametapolyphosphate is added and stirred for 1 hour, the mixture is allowed to stand for 0.5 hour, the upper suspension is filtered, and then dried and ground.
[0051] The preparation process is the same as that of Example 1. Example 3
[0052] A building joint sealing material is prepared from the following raw materials in parts by weight: 100 parts of polyurethane base glue, 14 parts of plasticizer, 27 parts of filler, 9 parts of reinforcing auxiliary agent, 0.09 parts of catalyst, 2.9 parts of latent curing agent, 1.3 parts of water remover and 1.4 parts of polyamide wax.
[0053] The plasticizer is dioctyl phthalate, the catalyst is dibutyltin dilaurate, the latent curing agent is ALT402, and the water scavenger is p-toluenesulfonyl isocyanate.
[0054] The filler is activated calcium carbonate, and the preparation process of activated calcium carbonate is as follows: put calcium carbonate into a ball mill, add 1.5% KH550 and 1.5% stearic acid by weight of calcium carbonate respectively, and ball mill at 500r / min for 30 minutes to obtain activated calcium carbonate.
[0055] The polyurethane base adhesive is prepared by the following steps:
[0056] (1) Add polyether diol (DL2000), polyether triol (3000) and epoxy resin into a three-necked flask, stir and heat to 120-125°C, and vacuum dry for 1 hour (vacuum degree -0.1Mpa);
[0057] (2) Cooling to 80°C, adding diphenylmethane diisocyanate, and polymerizing at 80-85°C for 3 hours; then adding polydimethylsiloxane and continuing to stir and react for 1 hour to obtain a polyurethane-based adhesive;
[0058] The weight ratio of polyether diol, polyether triol, diphenylmethane diisocyanate, epoxy resin and polydimethylsiloxane is 6:10:3:1:1.7. The polyether diol (DL2000), polyether triol (3000) and diphenylmethane diisocyanate are subjected to vacuum dehydration treatment before use.
[0059] The reinforcing agent is a composite material prepared by loading an antioxidant on an inorganic material, and its preparation process includes the following steps: dispersing the inorganic material in an acetone solution of the antioxidant 4010NA, evacuating the solution, immersing and adsorbing the solution for 40 minutes, and then filtering, drying, and grinding the solution to obtain the product; the weight ratio of the inorganic material to 4010NA is 4:1.
[0060] The above inorganic material is prepared by the following method:
[0061] (1) After removing impurities from sepiolite powder, the sepiolite powder was mixed with 3 mol / L hydrochloric acid solution at a weight ratio of 1:60 at 80°C and stirred for 10 hours, and then filtered, washed, dried, and ground to obtain acidified sepiolite; the acidified sepiolite was evenly mixed with deionized water at a weight ratio of 1:200, and then hydrothermally reacted at 150°C for 10 hours, and then filtered, washed, dried, and ground to obtain sepiolite fiber;
[0062] (2) Prepare 1 L of 0.50 mol / L Zn2SO4·7H2O solution, add 150 g of sepiolite fiber and stir evenly, slowly add 0.5 L of 1.6 mol / L NaOH solution while stirring, and then add KH550 (2% by weight of the sepiolite fiber). Place the mixed system in a water bath at 60°C and continue to age for 48 h. After filtering and drying, calcinate at 1050°C for 5 h to obtain an inorganic material.
[0063] The specific method of removing impurities from the sepiolite powder in step (1) is as follows: the sepiolite powder is mixed with water in a weight ratio of 1:12, the mixture is allowed to stand and soak for 24 hours, and then stirred for 3 hours; the mixture is allowed to stand and settle, and impurities at the bottom are removed during the filtration process; the filtration product is mixed with water in a weight ratio of 1:10, and then 0.25wt% sodium hexametapolyphosphate is added and stirred for 1 hour, the mixture is allowed to stand for 0.5 hour, the upper suspension is filtered, and then dried and ground.
[0064] The process is the same as that of Example 1. Example 4
[0065] A building joint sealing material is prepared from the following raw materials in parts by weight: 100 parts of polyurethane base glue, 14.5 parts of plasticizer, 28 parts of filler, 8.5 parts of reinforcing auxiliary agent, 0.09 parts of catalyst, 2.9 parts of latent curing agent, 1.4 parts of dewatering agent and 1.5 parts of polyamide wax.
[0066] The plasticizer is diisodecyl phthalate, the catalyst is dibutyltin dilaurate, the latent curing agent is ALT402, and the water scavenger is p-toluenesulfonyl isocyanate.
[0067] The filler is activated calcium carbonate, and the preparation process of activated calcium carbonate is as follows: put calcium carbonate into a ball mill, add 1.8% KH550 and 1.8% stearic acid by weight of calcium carbonate respectively, and ball mill at 500r / min for 30 minutes to obtain activated calcium carbonate.
[0068] The polyurethane base adhesive is prepared by the following steps:
[0069] (1) Add polyether diol (DL2000), polyether triol (3000) and epoxy resin into a three-necked flask, stir and heat to 120-125°C, and vacuum dry for 1 hour (vacuum degree -0.1Mpa);
[0070] (2) Cooling to 80°C, adding diphenylmethane diisocyanate, and polymerizing at 80-85°C for 3 hours; then adding polydimethylsiloxane and continuing to stir and react for 1 hour to obtain a polyurethane-based adhesive;
[0071] The weight ratio of polyether diol, polyether triol, diphenylmethane diisocyanate, epoxy resin and polydimethylsiloxane is 6:10:3:1:1.8. The polyether diol (DL2000), polyether triol (3000) and diphenylmethane diisocyanate are subjected to vacuum dehydration treatment before use.
[0072] The reinforcing agent is a composite material prepared by loading an antioxidant on an inorganic material, and its preparation process includes the following steps: dispersing the inorganic material in an acetone solution of 4010NA, evacuating the solution, impregnating and adsorbing the solution for 30-60 minutes, and then filtering, drying, and grinding the solution to obtain the product; the weight ratio of the inorganic material to 4010NA is 4:1.
[0073] The above inorganic material is prepared by the following method:
[0074] (1) After removing impurities from sepiolite powder, the sepiolite powder was mixed with 3 mol / L hydrochloric acid solution at a weight ratio of 1:60 at 80°C and stirred for 10 hours, and then filtered, washed, dried, and ground to obtain acidified sepiolite; the acidified sepiolite was evenly mixed with deionized water at a weight ratio of 1:200, and then hydrothermally reacted at 150°C for 10 hours, and then filtered, washed, dried, and ground to obtain sepiolite fiber;
[0075] (2) Prepare 1 L of 0.50 mol / L Zn2SO4·7H2O solution, add 150 g of sepiolite fiber and stir evenly, slowly add 0.5 L of 1.6 mol / L NaOH solution while stirring, and then add KH550 (2% by weight of the sepiolite fiber). Place the mixed system in a water bath at 60°C and continue to age for 48 h. After filtering and drying, calcinate at 1050°C for 5 h to obtain an inorganic material.
[0076] The specific method of removing impurities from the sepiolite powder in step (1) is as follows: the sepiolite powder is mixed with water in a weight ratio of 1:13, the mixture is allowed to stand and soak for 24 hours, and then stirred for 3 hours; the mixture is allowed to stand and settle, and impurities at the bottom are removed during the filtration process; the filtration product is mixed with water in a weight ratio of 1:10, and then 0.3wt% sodium hexametapolyphosphate is added and stirred for 1 hour, the mixture is allowed to stand for 0.5 hour, the upper suspension is filtered, and then dried and ground.
[0077] The preparation process is the same as that of Example 1. Example 5
[0078] A building joint sealing material is made of the following raw materials in parts by weight: 100 parts of polyurethane base glue, 15 parts of plasticizer, 30 parts of filler, 8 parts of reinforcing auxiliary agent, 0.1 part of catalyst, 3 parts of latent curing agent, 1.5 parts of water remover and 1.5 parts of polyamide wax.
[0079] The plasticizer is diisodecyl phthalate, the catalyst is dibutyltin dilaurate, the latent curing agent is ALT402, and the water scavenger is p-toluenesulfonyl isocyanate.
[0080] The filler is activated calcium carbonate, and the preparation process of activated calcium carbonate is as follows: put calcium carbonate into a ball mill, add 2% KH550 and 2% stearic acid by weight of calcium carbonate respectively, and ball mill at 500r / min for 30 minutes to obtain activated calcium carbonate.
[0081] The polyurethane base adhesive is prepared by the following steps:
[0082] (1) Add polyether diol (DL2000), polyether triol (3000) and epoxy resin into a three-necked flask, stir and heat to 120-125°C, and vacuum dry for 1 hour (vacuum degree -0.1Mpa);
[0083] (2) Cooling to 80°C, adding diphenylmethane diisocyanate, and polymerizing at 80-85°C for 3 hours; then adding polydimethylsiloxane and continuing to stir and react for 1 hour to obtain a polyurethane-based adhesive;
[0084] The weight ratio of polyether diol, polyether triol, diphenylmethane diisocyanate, epoxy resin and polydimethylsiloxane is 6:10:3:1:2. The polyether diol (DL2000), polyether triol (3000) and diphenylmethane diisocyanate are subjected to vacuum dehydration treatment before use.
[0085] The reinforcing agent is a composite material prepared by loading an antioxidant on an inorganic material, and its preparation process includes the following steps: dispersing the inorganic material in an acetone solution of 4010NA, evacuating the solution, impregnating and adsorbing the solution for 30-60 minutes, and then filtering, drying, and grinding the solution to obtain the product; the weight ratio of the inorganic material to 4010NA is 4:1.
[0086] The above inorganic material is prepared by the following method:
[0087] (1) After removing impurities from sepiolite powder, the sepiolite powder was mixed with 3 mol / L hydrochloric acid solution at a weight ratio of 1:60 at 80°C and stirred for 10 hours, and then filtered, washed, dried, and ground to obtain acidified sepiolite; the acidified sepiolite was evenly mixed with deionized water at a weight ratio of 1:200, and then hydrothermally reacted at 150°C for 10 hours, and then filtered, washed, dried, and ground to obtain sepiolite fiber;
[0088] (2) Prepare 1 L of 0.50 mol / L Zn2SO4·7H2O solution, add 150 g of sepiolite fiber and stir evenly, slowly add 0.5 L of 1.6 mol / L NaOH solution while stirring, and then add KH550 (2% by weight of the sepiolite fiber). Place the mixed system in a water bath at 60°C and continue to age for 48 h. After filtering and drying, calcinate at 1050°C for 5 h to obtain an inorganic material.
[0089] The specific method of removing impurities from the sepiolite powder in step (1) is as follows: the sepiolite powder is mixed with water in a weight ratio of 1:15, the mixture is allowed to stand and soak for 24 hours, and then stirred for 3 hours; the mixture is allowed to stand and settle, and impurities at the bottom are removed during the filtration process; the filtration product is mixed with water in a weight ratio of 1:10, and then 0.3wt% sodium hexametapolyphosphate is added and stirred for 1 hour, the mixture is allowed to stand for 0.5 hour, the upper suspension is filtered, and then dried and ground.
[0090] The preparation process is the same as that of Example 1.
[0091] Comparative Example 1
[0092] The difference between Comparative Example 1 and Example 5 is that the reinforcing auxiliary agent is replaced by a filler, that is, no reinforcing auxiliary agent is added.
[0093] Comparative Example 2
[0094] The difference between Comparative Example 2 and Example 5 is that the reinforcing agent is an inorganic material and the antioxidant 4010NA is not loaded.
[0095] Comparative Example 3
[0096] The difference between Comparative Example 3 and Example 5 is that the inorganic material in the reinforcing auxiliary agent does not carry zinc oxide whiskers, that is, the inorganic material is prepared by the following method:
[0097] After impurities are removed from the sepiolite powder, it is mixed with 3 mol / L hydrochloric acid solution at a weight ratio of 1:60 at 80°C and stirred for 10 hours, and then filtered, washed, dried and ground to obtain acidified sepiolite; after the acidified sepiolite is evenly mixed with deionized water at a weight ratio of 1:200, hydrothermally reacted at 150°C for 10 hours, filtered, washed, dried and ground to obtain sepiolite fiber, i.e., inorganic material.
[0098] Performance Testing
[0099] 1. Tensile strength and elongation at break: Cut the film cured for 7 days at (23±5)℃ and (55±5)%RH into dumbbell-shaped specimens and test them according to GB / T528-2009.
[0100] 2. Test of tensile bonding performance with concrete test blocks: (1) Prepare cement mortar test blocks with a size of 75*25*12mm, with a mix ratio of cement: sand and water of 1:2:0.4, and cure for 28 days after molding; (2) After two cement mortar test blocks are polished, they are placed parallel in the long direction (75mm), and plugged on both sides with wooden blocks (12.5*25*12mm) to form a cavity with a size of 50*25*12mm. Pour the joint sealing material of this application into it, filling 2 / 3 of the cavity. After self-leveling, cure at room temperature for 168h, remove the wooden block plugs on both sides to obtain the sample, and test the tensile bonding performance of the sample with a tensile testing machine.
[0101] 3. Aging resistance test; (1) Heat resistance: Place the test piece in a 70℃ environment, and take out one piece every 672h and 3000h for performance test. (2) Moisture and heat resistance: Place the test piece in a 70℃×95%RH high temperature and high humidity environment in a moist heat box, and take out one piece every 672h and 3000h for performance test. (3) UV aging resistance: Place the test piece in a UV aging box at 40℃, and take out one piece every 672h and 3000h for performance test.
[0102] Table 1 Performance test data
[0103]
[0104] As can be seen from Table 1, the tensile strength of the building joint sealing material prepared in this application is 4.20-4.52MPa, the elongation at break is 800-881%, and the tensile bonding performance can reach 3.7-4.05MPa, which shows that it has excellent mechanical properties, good deformation performance, and high bonding strength with concrete test blocks, and is more easily adapted to the requirements of different construction conditions. In Comparative Example 1, no reinforcing agent was added, and its tensile strength, elongation at break, and tensile bonding performance all decreased to varying degrees, indicating that the reinforcing agent in this application has a reinforcing and toughening effect on the sealant.
[0105] It can be seen from the results of the aging resistance test that, in the early stage, as the aging time increases, the polymer material is further slowly cross-linked, which improves the rigidity of the molecular chain. Therefore, the tensile strength of 672h detected during the aging test increases, but its elongation at break gradually decreases. As the aging time increases, its molecular chain gradually breaks at 3000h, and the tensile properties and elongation at break decrease, but the tensile strength and elongation at break loss rates of the sealing materials of Examples 1-5 of the present application are relatively low, indicating that its aging resistance is excellent; while no reinforcing agent is added in Comparative Example 1, the mechanical properties in the early stage of aging are worse than those of Example 5, and its mechanical properties are greatly reduced after the aging test, while the tensile strength and elongation at break loss rates of Comparative Examples 2 and 3 are less than those of Comparative Example 1, but much higher than those of Example 5, indicating that the reinforcing agent in the present application can greatly improve the aging resistance of the sealant, and the zinc oxide whisker and the antioxidant have the effect of synergistically increasing the aging resistance.
[0106] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Other modifications or equivalent substitutions made to the technical solution of the present invention by ordinary technicians in the field should be included in the scope of the claims of the present invention as long as they do not depart from the spirit and scope of the technical solution of the present invention.
Claims
1. A building joint sealing material, characterized in that: It is made of the following raw materials in parts by weight: 100 parts of polyurethane base glue, 12-15 parts of plasticizer, 25-30 parts of filler, 8-10 parts of reinforcing agent, 0.08-0.1 parts of catalyst, 2.8-3 parts of latent curing agent, 1-1.5 parts of dehydrating agent, and 1-1.5 parts of polyamide wax; The polyurethane base adhesive is prepared by the following steps: (1) Add polyether diol, polyether triol and epoxy resin into a three-necked flask, stir, heat to 120-125°C and vacuum dry for 1 hour; (2) Cooling to 80°C, adding diphenylmethane diisocyanate, and polymerizing at 80-85°C for 3 hours; then adding polydimethylsiloxane and continuing to stir and react for 1 hour to obtain a polyurethane-based adhesive; The weight ratio of the polyether diol, polyether triol, diphenylmethane diisocyanate, epoxy resin and polydimethylsiloxane is 6:10:3:1:1.5-2; The reinforcing agent is a composite material prepared by loading an antioxidant on an inorganic material, and the preparation method thereof comprises the following steps: dispersing the inorganic material in an acetone solution of the antioxidant 4010NA, evacuating the solution, impregnating and adsorbing the solution for 30-60 minutes, and then filtering, drying, and grinding the solution to obtain the product; the weight ratio of the inorganic material to the antioxidant 4010NA is 4:1; The inorganic material is prepared by the following steps: (1) After removing impurities from sepiolite powder, the sepiolite powder is mixed with a 3 mol / L hydrochloric acid solution at a weight ratio of 1:60 at 80°C and stirred for 8-10 hours, and then filtered, washed, dried, and ground to obtain acidified sepiolite; the acidified sepiolite is evenly mixed with deionized water at a weight ratio of 1:200, and then hydrothermally reacted at 150°C for 8-10 hours, and then filtered, washed, dried, and ground to obtain sepiolite fiber; (2) Prepare 1 L of 0.50 mol / L Zn2SO4·7H2O solution, add 150 g of sepiolite fiber and stir evenly, slowly add 0.5 L of 1.6 mol / L NaOH solution while stirring, then add 1.5-2% KH550 by weight of the sepiolite fiber, place the mixed system in a water bath at 60°C and continue to age for 48 h, filter and dry, and calcine at 1050°C for 5 h to obtain an inorganic material.
2. A building joint sealing material according to claim 1, characterized in that: The plasticizer is dioctyl phthalate or diisodecyl phthalate, the catalyst is dibutyltin dilaurate, the latent curing agent is ALT402, and the water scavenger is p-toluenesulfonyl isocyanate.
3. A building joint sealing material according to claim 1, characterized in that: The filler is activated calcium carbonate, and the preparation process of the activated calcium carbonate is as follows: putting calcium carbonate into a ball mill, adding 1-2% KH550 and 1-2% stearic acid by weight of calcium carbonate respectively, and ball milling at 500r / min for 30min to obtain activated calcium carbonate.
4. A preparation process of the building joint sealing material according to claim 1, characterized in that: The following steps are involved: Add polyurethane base glue, filler and reinforcing additive into a dispersion kettle and disperse for 1 hour, add other raw materials and mix for 30-40 minutes, and then discharge to obtain the product.
Citation Information
Patent Citations
Method for preparing polydimethyl siloxane / hydroxyl-terminated polybutadiene modified UV curing hyperbranched polyurethane
CN105585690A
Solvent-resistant epoxy modified polyurethane sealant and preparation method thereof
CN110172323A